Fun [compact disc] - Brooks, Garth; Yearwood, Trisha; Shelton, Blake; Pride, Charley (Pearl Records, 2020)
Garth Brooks's twelfth studio album features 14 tracks, including Dive Bar, the collaboration with Blake Shelton. The album also includes a cover of Shallow with Trisha Yearwood; All Day Long; and Stronger Than Me.